Typology of Unclassified Buildings and Specifics of Input Parameters for Energy Audits in Latvia. (June 2019) - Geikins, A; Borodinecs, A; Daksa, G; Bogdanovics, R; Zajecs, D
Abstract: The aim of the study is to analysis renovation solutions for unclassified buildings. According to Latvian law definition, unclassified buildings are prisons, security forces, police and fire services buildings including barracks, warehouse etc. Such buildings has completely different heat gains and heat losses balance and usage profile in comparison to traditional public and apartment buildings. Unclassified buildings could have higher internal heat and moisture loads, more strict requirements to dress code (CLO level), human metabolic equivalent and limited possibility for staff adaptation to IAQ parameters. The one of important factors is safety of energy supply and operation of HVAC systems. Although the energy security is a top priority for unclassified buildings, it should not be a barrier for implementation of renewable energy sources and innovative energy efficient retrofitting solutions in unclassified buildings.